1988
DOI: 10.1111/j.1476-5381.1988.tb11632.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that neutrophil accumulation induced by interleukin‐1 requires both local protein biosynthesis and neutrophil CD18 antigen expression in vivo

Abstract: Mechanisms involved in neutrophil accumulation induced by intradermal injection of interleukin‐1 (IL‐1) in the rabbit were investigated using intravenously‐injected 111In‐labelled neutrophils. C5a des Arg, N‐formyl‐methionyl‐leucyl‐phenylalanine (FMLP) and leukotriene B4 (LTB4) were included for comparison. Local inhibition of protein biosynthesis in the skin using actinomycin‐D or cycloheximide blocked 111In‐neutrophil accumulation induced by IL‐1, but not that induced by the other mediators. Actinomycin‐D an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 18 publications
5
52
0
Order By: Relevance
“…The proinflammatory cytokine IL-1␤ is a potent mediator of neutrophil accumulation in vivo, inducing local neutrophil accumulation after injection into a range of specific tissue sites (21)(22)(23). In 1989, Osborn et al (24) reported that IL-1 was able to augment the adhesiveness of the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…The proinflammatory cytokine IL-1␤ is a potent mediator of neutrophil accumulation in vivo, inducing local neutrophil accumulation after injection into a range of specific tissue sites (21)(22)(23). In 1989, Osborn et al (24) reported that IL-1 was able to augment the adhesiveness of the vascular endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…The CD18/P2 integrin family of adhesion molecules has been extensively studied both in vitro (Springer, 1990) and in vivo (Rampart & Williams, 1988;Nourshargh et al, 1989;1993a,b;Argenbright & Barton, 1992;Williams & Hellewell, 1992). Two members of the P2 integrin family, CDlIa/CD18 (LFA-1) and Cllb/CD18 (Mac-i) are widely held to be important in neutrophil adhesion at and migration to inflammatory sites.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…Studies have shown that antibodies raised against these molecules can be effective blockers of neutrophil adhesion in vitro (Sanchez-Madrid et al, 1983;Rothlein et al, 1986), and of inflammation in vivo (Arfors et al, 1987;Rampart & Williams, 1988;Barton et al, 1989;. Recently it has been shown that the Shwartzman reaction, a phenomenon that models disseminated intravascular coagulation, and non-immune complex mediated vasculitis, is both CD18 and ICAM-1 dependent (Argenbright & Barton, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…ing DNA-dependent RNA synthesis (Rampart & Williams, 1988;Colditz et al, 1989;Foster et al, 1989;Rampart et al, 1989). In this respect, IL-8 is considered to be a direct chemoattractant as are C5a and leukotriene B4.…”
Section: Introductionmentioning
confidence: 99%